Badminton Drop Shot and Smash Performance Across Standard and Non Standard Shuttlecocks - Burhan, Ahmad Syarif; Hasanuddin, M. Iqbal (Sportify Journal, 2022)
Shuttlecock quality is a critical but often underestimated factor in badminton skill development, particularly in local club settings where training equipment is frequently selected on the basis of cost and availability. This study examined differences in drop shot and smash performance when badminton athletes used standard and non-standard shuttlecocks. A quantitative comparative method with a repeated-measures experimental design was employed. Forty active athletes from Mandiri Husada Badminton Club, Palopo City, were selected through purposive sampling. Stroke performance was measured using three indicators: shuttlecock speed recorded by a radar gun, stroke accuracy assessed through a target-zone scoring system, and trajectory consistency analyzed through high-speed video-based kinematics. Each athlete completed structured drop shot and smash tests under both shuttlecock conditions, with a 48-hour washout period and counterbalanced testing order. Data were analyzed using the Shapiro-Wilk test, paired-samples t-test, and Cohen's d. The results showed that standard shuttlecocks produced significantly higher smash speed than non-standard shuttlecocks (142.3 km/h vs. 128.7 km/h; t (39) = 8.42; p < 0.001; d = 1.21). Drop shot accuracy was also substantially higher with standard shuttlecocks (78.4% vs. 61.9%; t (39) = 7.63; p < 0.001; d = 1.54). Trajectory consistency for both smash and drop shot was significantly more stable under the standard condition. These findings indicate that standard shuttlecocks provide more predictable mechanical and aerodynamic feedback, thereby supporting faster, more accurate, and more consistent stroke execution. Formal badminton training programs should prioritize BWF-standard shuttlecocks, especially for technical training and junior athlete development.